Economy of India - "Balasubramanyam, V. N." (London, 1984)
This book provides a succinct non-technical exposition of India's economic performance and policies. It is intended to help students who are trying to sift the vast literature with a view to gaining an understanding of India's economic problems and obtaining a perspective on the policy debates.
Keywords: India - economic conditions